Effects of ibrutinib on T-cell immunity in patients with chronic lymphocytic leukemia - Liu, Yanyan; Song, Yongping; Yin, Qingsong (Frontiers in Immunology, 2022)
Chronic lymphocytic leukemia (CLL), a highly heterogeneous B-cell malignancy prominently, is characterized by tumor microenvironment disorder and T-cell immune dysfunction, which play a major role in the proliferation and survival of CLL cells. Ibrutinib is the first irreversible inhibitor of Bruton’s tyrosine kinase (BTK). In addition to targeting B cell receptor (BCR) signaling to kill tumor cells, increasing evidence has suggested that ibrutinib regulates the tumor microenvironment and T cell immunity in a direct and indirect manner. For example, ibrutinib not only reverses the tumor microenvironment by blocking cytokine networks and toll-like receptor signaling, but also regulates T cells in number, subset distribution, T cell receptor (TCR) repertoire and immune function by inhibiting interleukin-2 inducible T cell kinase (ITK) and reducing the expression of inhibitory receptors, and so on. In this review, we summarize the current evidence for the effects of ibrutinib on the tumor microenvironment and cellular immunity of patients with CLL, particularly for the behavior and function of T cells, explore its potential mechanisms, and provide a basis for the clinical benefits of long-term ibrutinib treatment and the combined therapy based on T cell-based immunotherapies.